Fungos endofíticos de Piper Peltatum e Peperomia Pellucida: caracterização metabólitos secundários e atividades biológicas - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
A total of 282 endophytic fungi were collected from these two plants, which were classiﬁed into 19 groups according to their morphological characteristics. Of these groups, 12 had their genus identiﬁed (Penicillium, Fusarium, Colletotrichum, Guignardia, Phomopsis, Cephalosporium, Bionectria, Xylaria, Aspergillus, Lirula, Pestalotiopsis and Trichoderma). Five strains (Penicillium, Fusarium, Cephalosporium, and two Xylaria) were selected for large-scale culture, whose extracts were fractionated. Fiveisolatedsubstanceswereidentiﬁed(austdiol19-20epoxycytochalasin Q, cytochalasin D, 7-decloro griseofulvin and 5-methoxycarbonyl-melein), one of which – austdiol – was produced in large quantities by a fungus of the Fusarium genus, which is the ﬁrst report of this substance being produced by a fungus of the Hypocreales class. The endophytic fungi proved be a good source of substances with biological activity.
Keywords: Produtos naturais; Metabólicos secundários; Fungos endofíticos; CIÊNCIAS EXATAS E DA TERRA: QUÍMICA